2022
DOI: 10.1007/s10951-022-00721-1
|View full text |Cite
|
Sign up to set email alerts
|

Exact and meta-heuristic approaches for the production leveling problem

Abstract: In this paper, we introduce a new problem in the field of production planning, called the production leveling problem. The task is to assign orders to production periods such that the load in each period and for each product type is balanced, capacity limits are not exceeded, and the orders’ priorities are taken into account. Production leveling is an important intermediate step between long-term planning and the final scheduling of orders within a production period, as it is responsible for selecting good sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…An optimised line was developed using mixed-integer linear programming for manufacturing a specific product family with a set of product variants and a new product incorporated after a time span. Vass et al. (2022) proposed a meta-heuristic approach to the production levelling problem.…”
Section: Production Levelling and Operational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…An optimised line was developed using mixed-integer linear programming for manufacturing a specific product family with a set of product variants and a new product incorporated after a time span. Vass et al. (2022) proposed a meta-heuristic approach to the production levelling problem.…”
Section: Production Levelling and Operational Performancementioning
confidence: 99%
“…An optimised line was developed using mixed-integer linear programming for manufacturing a specific product family with a set of product variants and a new product incorporated after a time span. Vass et al (2022) proposed a meta-heuristic approach to the production levelling problem. They demonstrated that meta-heuristic techniques have the potential to address planning challenges associated with achieving a work-balancing objective, managing multiple production capacity restrictions and optimising order priorities.…”
Section: Production Levelling and Operational Performance 21 Review O...mentioning
confidence: 99%